Hubungan Posisi Perawat Dalam Melakukan Pasien Handling Transfer Bed Terhadap Keluhan Nyeri Punggung Bawah Perawat di Rumah Sakit Reksa Waluya Mojokerto - Adi Purnomo; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad Abdullah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: One of the activities that are at risk for the occurrence of LBP is lifting and mobilizing the patient. Activities performed by nurses will create or increase stress on the arms, shoulders, legs, and back.This study aims to analyze the relationship between nurse's position in handling transfer bed patients towards complaints of low back pain.Methods: The independent variable in this study was the position of the nurse in carrying out patient handling transfer beds, while the dependent variable was low back pain (LBP). Respondents in this study amounted to 78 people using purposive sampling technique. This research design uses a cross sectional studyResults: The results of this study are p-value = 0.0711 (p <1) which means that there is a relationship of nurse position in doing patient handling transfer bed towards complaints of lower back pain (LBP) at Hospital Reksa Waluya Mojokerto 2021.Conclusion: There is a relationship between the position of nurses in carrying out patient handling transfer beds with complaints of low back pain by nurses at Reksa Waluya Hospital, Mojokerto with a p-value / r = 0.0711, which means that there is a strong correlation(0,6 ≤ r ≤0,8)